PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN PADA RESTORAN LAMUN OMBAK KOTA PADANG - Kurnia Illahi Manvi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
Padang Restaurant business today shows a relatively rapid development, proven by the increasing number of Padang Restaurants in Indonesia. This indicates that the intensity of competition in the restaurant business is getting stronger. The tendency of people or customer eating in the Padang restaurant is considered to have its own taste, which is able to provide a place in the hearts of food lovers. This kind of opportunity is used by the Lamun Ombak Restaurant to provide a service model that is really needed by the surrounding community. The variety of products and service systems for the Lamun Ombak Restaurant, in fact, can relatively influence purchasing decisions so that maximum customer satisfaction can be created. This study aims to determine the effect of the marketing mix on customer satisfaction at Lamun Ombak Restaurant. The research design used surveys and research methods which are associative methods. The research instrument uses a Likert scale, and the analysis technique uses multiple linear regressions, considering the model is composed of a number of causal relationships between latent variables. Keywords: marketing mix, restaurant, customer satisfaction.